Analysis of formal characteristics of text in the CPACT Research: Enhancing the LIWC linguistic processing for the Czech language - DALIBOR KUCERA; JIRI HAVIGER (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This paper describes how psycholinguistic and psychodiagnostic fields have adopted quantitative text analysis to process spoken Czech. This method employs computer-assisted linguistic procedures to categorize and quantify formal characteristics (such as morphology, semantics, etc.) of recorded texts.Method: The study’s sample size is 200 people who were selected using age, gender, and level of education to reflect the same proportion of representation of the target groups as is found in the total Czech population. The processes of lemmatization (the identification of a lexical unit as a dictionary entry) and unambiguity (the removal of ambiguity in interpreting a particular word or homonymy) are used in formal text analysis.Findings: In total, CPACT studies use 212 linguistic variables, which is a substantial number. So the output is much larger than the Linguistic Processes module in the LIWC 2015 program, which processes 29 grammatical/summary variables. The linguistic variables processed by LIWC are limited, but the grammatical categories and subcategories used in the CPACT study allow for a much more in-depth exploratory study.Implications/Novel Contribution: The results of this study provide new information on the experimental application of quantitative psycholinguistic analysis to formal parameters. It’s a fascinating strategy, and it yields many interesting hypotheses and study directions. Research into this area, whether by linguists or psychologists, has the potential to reveal surprising new insights into the makeup and dynamics of human communication.